2023
DOI: 10.1007/s00167-023-07308-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased medial posterior tibial slope is associated with an increased risk of posterior cruciate ligament rupture

Abstract: Purpose It remains unclear whether there is an association between posterior cruciate ligament (PCL) rupture and the medial posterior tibial slope (MTS) or lateral posterior tibial slope (LTS). The present case-control study aimed to investigate a possible association between primary PCL rupture and MTS or LTS measured by magnetic resonance imaging (MRI). Methods A retrospective case-control study was conducted. Patients with primary PCL ruptures but not with anterior cruciate ligament injuries, were 1:1 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…One study found that the 10‐year graft survival rates were 50% for those with an LTS of ≤3.8 versus 91.7% for an LTS of >3.8 ( p = 0.001) [26]. Three studies reported a mean LTS of 5.0 (range: 4.4–5.5) degrees in the PCL rupture group and 5.7 (range: 5.3–6.4) degrees in the control group [17, 18, 22]. Two studies found no significant difference in LTS between the PCL rupture and control groups [17, 22], while one study found that patients with PCL ruptures had significantly flatter LTS compared to controls ( p = 0.009) [18].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study found that the 10‐year graft survival rates were 50% for those with an LTS of ≤3.8 versus 91.7% for an LTS of >3.8 ( p = 0.001) [26]. Three studies reported a mean LTS of 5.0 (range: 4.4–5.5) degrees in the PCL rupture group and 5.7 (range: 5.3–6.4) degrees in the control group [17, 18, 22]. Two studies found no significant difference in LTS between the PCL rupture and control groups [17, 22], while one study found that patients with PCL ruptures had significantly flatter LTS compared to controls ( p = 0.009) [18].…”
Section: Resultsmentioning
confidence: 99%
“…One study found that the 10‐year graft survival rates were 68.4% for patients with an MTS of ≤5.6° versus 92.6% for patients with an MTS of >5.6° ( p = 0.029) [26]. Four studies reported a mean MTS of 4.3 (range: 3.0–7.0) degrees in the PCL rupture or graft failure group and 6.5 (range: 5.0–9.2) degrees in the control group [17, 18, 22, 25]. All four studies found that patients with PCL injury had significantly flatter MTS than controls ( p < 0.001, p = 0.014, p = 0.023, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations